The Pathophysiological Skin Changes Associated with Chronic Venous Insufficiency and the Use of Negative Pressure Wound Therapy - Boxall, Sharon Lee (Curtin University, 2023)
This thesis consisted of three investigations: a study comparing the efficacy of compression bandaging and single use negative pressure wound therapy to compression bandaging alone in the treatment of venous leg ulcers, an investigation of the sub-bandage pressures beneath compression therapy and single use negative pressure wound therapy and an exploration of the differences in skin morphology and protein expression between healthy skin and that affected by chronic venous insufficiency.